1986
DOI: 10.1038/clpt.1986.63
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine tablet vs. hydralazine in patients with persisting hypertension who receive combined diuretic and beta-blocker therapy

Abstract: The antihypertensive effects of a 20 mg tablet of nifedipine were compared with those of hydralazine in a randomized, double-blind, placebo-controlled study. Nineteen patients with a diastolic blood pressure (BP) between 95 and 120 mm Hg despite combined diuretic and beta-blocker therapy completed the protocol. After 2 weeks of placebo each subject received increasing doses of nifedipine (20, 40, and 60 mg b.i.d.) and hydralazine (25, 50, and 100 mg b.i.d.) if tolerated or until goal BP (supine and standing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As in our previously reported study [17], both drugs lowered BP, but nifedipine was significantly more effective than hydralazine in lowering systolic BP in this Values represent means = SEM (n -6), reported as the absolute values on placeb~ and the changes induced by nifedipine or hydralazine. EDV = LV end-diastolic volume.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As in our previously reported study [17], both drugs lowered BP, but nifedipine was significantly more effective than hydralazine in lowering systolic BP in this Values represent means = SEM (n -6), reported as the absolute values on placeb~ and the changes induced by nifedipine or hydralazine. EDV = LV end-diastolic volume.…”
Section: Discussionmentioning
confidence: 65%
“…Since arterial vasodilators such as hydralazine are generally used as part of a triple-therapy regimen [16], our studies focused on differences between the two classes of vasodilators persisting with combination therapy. Previously, we examined the antihypertensive efficacy of nifedipine tablets versus hydralazine in patients with hypertension persisting on combined diuretic and beta-blocker therapy; nifedipine was clearly more effective than hydralazine in lowering systolic BP [17]. We now report on the effects of nifedipine versus hydralazine on plasma catecholamines, ptasms renin activity (PRA), and left ventricular (LV) systolic and diastolic function.…”
mentioning
confidence: 94%
“…This case against nifedipine is not yet proven. Hypokalemia, although found in one study when nifedipine was combined with a diuretic and ~]blocker [30], could not be found in another study when a similar combination was made [31]. Sometimes glucose tolerance may actually improve [28].…”
Section: Nifedipine Side Effectsmentioning
confidence: 95%
“…29 31 However, a few studies did suggest that add-on therapy with a DHP-CCB was more efficacious than add-on therapy with hydralazine. 32 –34…”
Section: Hydralazinementioning
confidence: 99%